Effects of Smilaxchinoside A and Smilaxchinoside C, Two Steroidal Glycosides from Smilax riparia, on Hyperuricemia in a Mouse Model. (6th August 2014) - Wu, Xiao‐Hui; Wang, Chong‐Zhi; Zhang, Jun; Wang, Shu‐Qing; Han, Lide; Zhang, Yan‐Wen; Yuan, Chun‐Su
<x xml:space="preserve">Abstract</x> The roots and rhizomes of Smilax riparia, called 'Niu‐Wei‐Cai' in traditional Chinese medicine, are believed to be effective in treating the symptoms of gout. However, the active constituents and their uricosuric mechanisms are unknown. In this study, we isolated two steroidal glycosides, named smilaxchinoside A and smilaxchinoside C, from the total saponins obtained from the ethanol extract of the roots of S. riparia. We then examined if these two compounds were effective in reducing serum uric acid levels in a hyperuricemic mouse model induced by potassium oxonate. We observed that these two steroidal glycosides possess potent uricosuric activities, and the observed effects accompanied the reduction of renal mURAT1 and the inhibition of xanthine oxidase, which contribute to the enhancement of uric acid excretion and the reduction of hyperuricemia‐induced renal dysfunction. Smilaxchinoside A and smilaxchinoside C may have a clinical utility in treating gout and other medical conditions caused by hyperuricemia. Copyright © 2014 John Wiley & Sons, Ltd.